Pengaruh Sosialisasi Terhadap Tax Amnesty Dengan Risiko Offshore Investment dan Kemudahan Prosedur Sebagai Pemoderasi - Nanda, A.A. Istri Syania Vihira; Noviari, Naniek (E-Jurnal Akuntansi; Vol 30 No 2 (2020)DO - 10.24843/EJA.2020.v30.i02.p01, 2020)
This reaserch aims to obtain empirical evidence of the effect of taxation socialization on tax amnesty as well as moderation of ease of procedures and the risk of offshore investment on the effect of tax socialization on tax amnesty. This research was conducted on taxpayers registered at the North Badung Primary Tax Service Office with a convenience sampling method. The analysis technique used is binary logistic regression with moderating regression analysis (MRA). Based on the results of this study indicate that taxation socialization has a significant positive effect on tax amnesty which means the higher the taxation socialization, the higher the tax amnesty participation. The interaction between ease of procedure and taxation socialization has a significant positive effect, which means that ease of procedure is able to strengthen the relationship between taxation socialization and tax amnesty. The interaction of offshore investment risks has a positive but not significant effect on tax amnesty which means that offshore investment risks are not able to strengthen the relationship of tax socialization to tax amnesty. Keywords: Tax Amnesty; Ease of Procedure; Offshore Investment Risk.